An Anisotropic Elastic-plastic Model for the Optimization of a Press Machine’s Auxiliary Worktable Plate Thickness - Rajhi, W.; Ayadi, B.; Alghamdi, A.; Messaoudene, N. (Engineering, Technology & Applied Science Research, 2018)
In this work an anisotropic elastic–plastic finite element model strongly coupled with ductile damage is applied to determine the suitable thickness of added auxiliary worktable plate to a 100 ton maximum capacity press machine. The major focus of this study is to minimize the amount of stress transmitted to the optional worktable plate and the press machine body while allowing them to withstand plastic deformation and damage during compression testing until final sample fracture. The worktable plates and the press machine body are made of TRIP800 grade steel. AISI 316L stainless steel is chosen as test material for the cylindrical billets. The proposed model is based on a non-associative plasticity theory and the “Hill 1948” quadratic (equivalent) stress norm is considered to describe the large plastic anisotropic flow accounting for mixed isotropic and kinematic hardening with isotropic damage effect. For each material the model uses an experimental data base obtained from a set of tensile tests conducted until the final fracture in three directions, the rolling direction (RD) or 0, the transverse direction (TD) or 90, and the 45 direction. After several numerical simulations of compression testing using ABAQUS/Explicit FE® software, thanks to the user’s developed VUMAT subroutine, varying cylindrical billet diameters and material, worktable plates number and thicknesses and spatial plate configurations the solution of 100mm thick worktable plate is selected since in that case the cylinder specimen is totally damaged and the stress state inside the worktable plates and the press machine body remains admissible.